A comparison of deep drawing and ironing of metal alloy strip produced conventionally and non-conventionally via semi solid material processing - Lima Filho, Antonio De Pádua [UNESP]; Yamasaki, Márcio Luji [UNESP]; Ono, Leandro Akita [UNESP]; Nampo, Lourenço; Padilha, Alcides [UNESP] (My University, 2008)
A semi solid thin strip continuous casting process was used to obtain 50%wt Pb/50%wtSn strip by single and twin roll processing at speed of 15 m/min. A 50%wt Pb/50%wtSn plate ingot was also cast for rolling conventionally into strips of 1.4 mm thickness and 45 mm width for comparison with those achieved non-conventionally. This hypoeutectic alloy has a solidification interval and fusion temperature of approximately 31°C and 215°C respectively. The casting alloy temperature was around 280°C as measured by a type K immersion thermocouple prior to pouring into a tundish designed to maintain a constant melt flow on the cooling slope during semi solid material production. A nozzle with a weir ensures that the semi solid material is dragged smoothly by the lower roll, producing strip with minimum contamination of slag/oxide. The temperatures of the cooling slope and the lower roll were also monitored using K type thermocouples. The coiled semi solid strip, which has a thickness of 1.5 mm and 45 mm width, was rolled conventionally in order to obtain 1.2 mm thick strip. The coiled thixorolled strip had a thickness of 1.2 mm and achieved practically the same width as the conventional strips. Blanks of 40 mm diameter were cut from the strips in a mechanical press, ready for deep drawing and ironing for mechanical characterization. All the strips achieved from non-conventional processing had the same mechanical performance as those achieved conventionally. The limiting drawing ratio (LDR) achieved was approximately 2.0 for all strips. Microscopy examination was made in order to observe phase segregation during processing.
Keywords: Deep drawing; Ironing; Pb50%Sn alloy; Semi-solid strip casting